2020
DOI: 10.1101/2020.07.27.224287
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Laser induced isolation and cultivation of single microbial cells

Abstract: Single cell isolation and cultivation play an important role in studying physiology, gene expression and functions of microorganisms. Laser Induced Forward Transfer Technique (LIFT) has been applied to isolate single cells but the cell viability after sorting is unclear. We demonstrate that a three-layer LIFT system could be applied to isolate single cells of Gram-negative (E. coli), Gram-positive (Lactobacillus rhamnosus GG, LGG), and eukaryotic microorganisms (Saccharomyces cerevisiae) and the sorted single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
1
1
Order By: Relevance
“…In this work, upon 95% yeast in control group can survive, which could be explained by the fact that the yeast cells were in a sterile and humid environment during the entire operation process. Moreover, lower laser energy for sorting was used than Liu et al reported [21], Liu et al reported 58% S. cerevisiae survived after sorting by LIFT, which was much lower than the result of 84% ± 3% in this work. The low damage to target cells of the present method favors the sorting of single cell and other subsequent single-cell research work.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In this work, upon 95% yeast in control group can survive, which could be explained by the fact that the yeast cells were in a sterile and humid environment during the entire operation process. Moreover, lower laser energy for sorting was used than Liu et al reported [21], Liu et al reported 58% S. cerevisiae survived after sorting by LIFT, which was much lower than the result of 84% ± 3% in this work. The low damage to target cells of the present method favors the sorting of single cell and other subsequent single-cell research work.…”
Section: Discussioncontrasting
confidence: 66%
“…Liang et al had sorted three microorganisms including S. cerevisiae, Escherichia coli, and Lactobacillus rhamnosus GG by a three-layer LIFT system. The average re-cultivation ratio reached 58%, 22%, and 74%, respectively [21]. It made it possible to sort target microorganisms accurately, though the average re-cultivation rate still needed to promote.…”
Section: Introductionmentioning
confidence: 99%